PENGARUH KERJASAMA INDONESIA DAN FILIPINA DALAM MENGATASI PENANGKAPAN IKAN ILEGAL DI WILAYAH PERBATASAN PERAIRAN KEDUA NEGARA - Oktari, Wulan Dwi; Olivia, Yessi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This paper describes the effect of fishing cooperation between the Republic of Indonesia andthe Philippines in addressing IUU Illegal Fishing in waters lie within the borders of both countriesin theSulawesi Sea. Because of the proximity of the geographical location of both countries andboth feel harmed by illegal IUU fishing, the two countries commit bilateral cooperation inaddressing this problem.All the data and statistics were gathered from books, journals and the internet. This paperuses International Cooperation theory by K.J Holsti, that tell about how the cooperation betweenboth countries runs.This study shows that the cooperation between both countries have a significant differencesabout the amount of IUU Illegal Fishing cases. IUU Illegal Fishing cases pressed till the lowestlevel every years. It makes the level of fisheries productivity grows high and nations income rises.Keyword: IUU Fishing Illegal, Cooperation, Sulawesi Sea, MoU